1875 Wyo. Terr. Sess. Laws ch. 52, §1 - (:unkn) unknown (My University, 1875)
Prohibited the carry of any firearm or other deadly weapon with any city, town, or village.
Keywords: CARRY - CERTAIN PUBLIC PLACES